Factors Affecting Inactive BPJS Participants in the UPTD of Sungai Raya Community Health Center, East Aceh Regency - Efri Gustina; Asriwati Amirah; Nur Aini (Newinera Publisher, 2022)
Based on data from BPJS Health in 2019, it reached a membership number of 221,580,743 people. However, in reality, many patients who are about to provide health services at Hekath Centre are found to have an inactive membership card. The study aimed to determine the effect of vulnerability, seriousness, barriers, perceived benefits, influence to act and dominant factors on BPJS Inactive Membership. The study was an analytical survey with a cross-sectional approach.. The population were 50 people and the sampling technique used an accidental technique with a purposive approach. Data analysis used univariate, bivariate and multivariate. The results showed that the multivariate p(sig) susceptibility value was .532 (OR=2.515 CI 0.140-45.253), confidence was .032 (OR=16,712 CI 1.275-219.028), benefits were .015 (OR=28,388 CI 1.942-415.210), barriers of .015 (OR=23,558 CI 1.863-297.969), the effect of acting was 0.353 (OR=4.119 CI .208-81.681). In conclusion, the variables that simultaneously influence the inactive BPJS membership were beliefs, benefits and obstacles, while the most dominant factor for the inactive BPJS membership is the perceived benefits. BPJS Health must increase the quantity of socialization. This can be seen from the lack of continuous socialization to the community of BPJS members by installing banners containing the slogan of the JKN Program so that it must be reproduced and installed in every health facility.